Towards high resolution absolute angle sensing using dual-wavelength laser speckle - Gibson, Sam J.; Charrett, Thomas O. H.; Tatum, Ralph P. (Institute of Electrical and Electronics Engineers (IEEE), 2024)
We present a two dimensional angle sensor with greater than 0.01 degrees resolution, using dual-wavelength laser speckle. The technique uses speckle correlation of a double speckle pattern, determining absolute surface tilt from a single frame. A constructed sensor was used to measure a grid of 2D angles between ±0.25° rotating around both x and y axes. Sensor performance was limited by laser mode instability effects, however an analysis of measurements demonstrated that a stable mode output could achieve bias errors of less than 0.010°, and standard deviations of 0.003° around x and 0.021° around y .
Keywords: Surface waves; Wavelength measurement; Measurement by laser beam; Surface emitting lasers; Speckle; Laser stability; Robot sensing systems